Performance of young pigs as affected by energy density of and method of adding fat to rations - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty-six crossbred pigs averaging 11.7 kg. (25.7 lbs.) were used to determine the effects of energy density (added fat or fiber) and calorie-protein, calorie-lysine, and calorie-nutrient ratios of rations on pig performance. The basal sorghum-soybean meal ration contained 16.0% crude protein, 0.80% lysine, 0.70% calcium, and 0.60% phosphorus. Soybean oil was the fat source and cellulose the fiber source. Adding 6% fat and maintaining a constant calorie-lysine, calorie-protein, or calorie-nutrient ratio increased (P<.05) average daily gain and improved (P<.05) feed efficiency, compared with gain and efficiency of pigs fed the basal ration. Pigs fed rations containing 6% fiber had similar average daily gain and feed efficiency as did pigs feed the basal ration.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Performance; Energy density; Fat; Rations; Feed efficiency; Average daily gain